The basic helix-loop-helix transcription factor MYC1 is involved in the regulation of the flavonoid biosynthesis pathway in grapevine - Hichri, Imène; Heppel, Simon; Czemmel, Stefan; Bogs, Jochen (Molecular plant, 2010)
Previous results indicated that in grapevine (Vitis vinifera), regulation of the flavonoid pathway genes by MYB transcription factors depends on their interaction with basic helix-loop-helix proteins (bHLHs). The present study describes the first functional characterization of a bHLH factor from grapevine named VvMYC1. This transcription factor is phylogenetically related to Arabidopsis bHLH proteins, which participate in the control of flavonoid biosynthesis and epidermal cell fate. Transient promoter and yeast two-hybrid assays demonstrated that VvMYC1 physically interacts with MYB5a, MYB5b, MYBA1/A2, and MYBPA1 to induce promoters of flavonoid pathway genes involved in anthocyanin and/or proanthocyanidin (PA) synthesis. Additionally, transient promoter assays revealed that VvMYC1 is involved in feedback regulation of its own expression. Transcript levels of VvMYC1 during berry development correlate with the synthesis of anthocyanins and PAs in skins and seeds of berries, suggesting that VvMYC1 is involved in the regulation of anthocyanins and PA synthesis in these organs. Likewise, transient expression of VvMYC1 and VvMYBA1 induces anthocyanin synthesis in grapevine suspension cells. These results suggest that VvMYC1 is part of the transcriptional cascade controlling anthocyanin and PA biosynthesis in grapevine.